Long, Regular Return of Four Large Earthquakes on Qilian Shan's Minle‐Damaying Frontal Thrust (NE Tibet): Partial Clustering With Great Events on the Leng Long Ling Fault?. Issue 5 (5th May 2022) - Li, Zhanfei; Xu, Xiwei; Tapponnier, Paul; Chen, Guihua; Ren, Junjie; Li, Kang; Cheng, Jia; Kang, Wenjun; Luo, Jiahong
Abstract: The exact geometry and rupture behavior of the Minle‐Damaying Thrust (MDT), along NE Tibet's Qilian Shan's mountain front, remain unclear. Based on a new ∼45 km long, ∼2.5 km wide, and 0.5 m resolution Unmanned Aerial Vehicle survey of the thrust's eastern part, we accurately map its surface trace in order to identify and quantify the sizes of large post‐glacial earthquakes. Our geomorphic measurements (72 vertical offsets [VOs] ranging from 1.2 to 13.8 m) validated by fieldwork, reveal four distinct peak throw clusters (∼2.2, 5.4, 8.3, 11.6 m) along the slightly stepping, frontal strands of the foreland‐propagating thrust trace. Shallow thrust dip‐angles constrained by the three‐point method at five sites range from ∼32° to 43°. Anchoring our 72 throw measurements to previous dating results and paleo‐seismological trench logs at the Xie river site, implies that the MDT's eastern segment broke regularly with ∼2.9 +0.6 /−0.8 m of nearly characteristic average VO (∼4.9 m of slip) to produce Mw ∼ 7.0–7.4 earthquakes, with a return time of ∼3.6 +0.8 /−1.0 ka since ∼12.7 ka. Paleo‐seismological results suggest that the occurrence of thrust earthquakes on the MDT may be coupled with that of large strike‐slip events, similar to the 1927, Mw ∼ 8, Gulang earthquake on the neighboring (∼18 km SW) Leng Long Ling segment of the Haiyuan Fault. That co‐seismic slip on the latter might control ∼ coeval slip along the sub‐parallel MDT may reflect a rupture behavior dictated by their partitioning/bifurcation at ∼20 km depth, close to their adjacent, restraining, left‐stepping bends. Plain Language Summary: New high‐resolution (0.5 m) topographic data along the eastern Qilian Shan's Minle‐Damaying frontal thrust (MDT) reveals a slightly stepping fault trace. Vertical offset measurements imply ∼ similar slip (∼4.9 m) during four Mw ∼ 7.0–7.4 earthquakes with return times of ∼3.6 +0.8 /−1.0 ka since ∼12.7 ka. The temporal and spatial distributions of large earthquakes around Northeast Tibet's corner suggest coupled, clustered release of regional strain between the MDT and the adjacent Leng Long Ling segment of the left‐lateral Haiyuan strike‐slip Fault. This is consistent with slip‐partitioning between these two sub‐parallel crustal faults that may merge downdip at ∼20 km depth, and with the synchronous rupturing of the Leng Long Ling fault and South Wuwei Thrust during the M ∼ 8 1927 Gulang Earthquake. Key Points: 0.5 m resolution Unmanned Aerial Vehicle mapping of the ∼45 km‐long, surface trace of the active, 36 ± 8° SW‐dipping, eastern Minle‐Damaying Thrust (MDT) (NE Qilian Shan) Since ∼12.7 ka, four large earthquakes with estimated Mw ∼ 7.0–7.4 and ∼2.9 +0.6 /−0.8 m average throws ruptured the eastern MDT, with estimated recurrence intervals of 3.6 +0.8 /−1.0 ka Some MDT thrust events might be coupled with great earthquakes (e.g., 1927) along the adjacent, sub‐parallel Leng Long Ling‐Haiyuan strike slip fault